Pyrolysis of biomass - Wang, Shurong (GREEN alternative energy resources ;, 2017)
Biomass is considered to be a prime option as an alternative to fossil stock for fuels and chemicals. This book explores the pyrolysis behavior of cellulose, hemicellulose and lignin. It discusses the influence of component interactions, mineral salts and catalysts on biomass pyrolysis. It also introduces bio-oil upgrading based on molecular distillation. Enriched with numerous case studies, the book provides fundamental reference for bioenergy researchers and industrial engineers.